The Euro and SUT-RAS methods: some further considerations. Issue 2 (3rd April 2021) - Valderas-Jaramillo, Juan Manuel; Rueda-Cantuche, José Manuel; Beutel, Joerg
Abstract : The main objective of this paper is to revisit the Euro method in a critical and constructive way. We have analysed some arguments against the Euro method published recently in the literature as well as some other relevant aspects of the SUT-Euro and SUT-RAS methods not covered before. Although not being the Euro method perfect, we believe that there is still space for the use of the Euro method in updating/regionalizing Supply and Use tables.